Micromechanical investigation of liquefaction of granular media by cyclic 3D DEM tests. Issue 10 (13th October 2020) - Martin, Eduardo L.; Thornton, Colin; Utili, Stefano
Abstract : In order to evaluate numerically the seismic-induced liquefaction potential of gravelly soils, three-dimensional discrete-element method cyclic undrained triaxial tests were performed in a periodic cell. The undrained tests were conducted by deforming the samples under constant volume conditions. The paper presents a detailed investigation into the mechanical phenomena occurring at the grain scale leading to the liquefaction of gravel when subjected to cyclic straining. The influence of variables characterising the granular assembly, such as inertial number, geometrical coordination number, mechanical coordination number, redundancy index and Reynolds stresses, on liquefaction is investigated. Results of the simulations show that the onset of liquefaction occurs when the granular medium becomes on average isostatic – that is the redundancy index is equal to 1, the geometrical coordination number is equal to 2 and the mechanical coordination number is equal to 3. To elucidate further the transition from solid-like to liquid-like behaviour, an analysis of how particles cluster together is presented. It is shown that, as the mean effective stress decreases, contacts are lost, with the maximum cluster size gradually reducing at an increasing rate. The loss of contacts is uniformly distributed throughout the sample and there is no break-up of the largest cluster into smaller clusters.